2010
DOI: 10.1016/j.tig.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Interchromosomal association and gene regulation in trans

Abstract: The nucleus is an ordered three-dimensional entity, and organization of the genome within the nuclear space might have implications for orchestrating gene expression. Recent technological developments have revealed that chromatin is folded into loops bringing distal regulatory elements into intimate contact with the genes that they regulate. Such intrachromosomal contacts appear to be a general mechanism of enhancer-promoter communication 'in cis'. Tantalizing evidence is also emerging that regulatory elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 98 publications
2
89
0
2
Order By: Relevance
“…Transcriptional regulation of genes can occur in a coordinated manner to ensure simultaneous regulation. For this purpose, gene loci come in proximity and are regulated by the same transcriptional machinery (71). mir-155 has been previously shown to participate in such transcription factories upon TNF-a stimulation (72).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulation of genes can occur in a coordinated manner to ensure simultaneous regulation. For this purpose, gene loci come in proximity and are regulated by the same transcriptional machinery (71). mir-155 has been previously shown to participate in such transcription factories upon TNF-a stimulation (72).…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive analyses based on DNA fluorescence in situ hybridization (DNA FISH) and chromatin conformation capture (3C) have shown that the threedimensional organization of the nucleus involves physical interactions between distant genomic regions, suggesting that gene regulation is more complex than this simplified model (reviewed by Gondor and Ohlsson 2009;Naumova and Dekker 2010). Further complicating our view, long-distance interactions are not limited to genomic regions on the same chromosomes (in cis), but are also observed between specific loci on separate chromosomes (in trans) (reviewed by Williams et al 2010). Through genome-wide 3C-based approaches, extensive interchromosomal interactions have been identified in yeast (Duan et al 2010), Drosophila (Sexton et al 2012), mice (Zhang et al 2012), and humans (LiebermanAiden et al 2009) and are thus a component of nuclear organization in diverse organisms.…”
mentioning
confidence: 99%
“…3,4 Besides pointing to a new "chromatinhub" model of gene regulation in which promoters, enhancers, LCRs and boundary elements all interact through DNA looping, these new methods are forcing us to consider new possibilities of genome "interactomes", whereby co-regulation of both small and large gene sets occurs through long-range interactions mediated by common sets of transcription factors and cofactors.…”
mentioning
confidence: 99%